2008
DOI: 10.1159/000161116
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Histopathology Reporting of Melanoma in a High-Incidence Geographical Region

Abstract: Background: Appropriate histopathology reporting helps to ensure effective therapy and prognosis. Objective: Toexamine compliance with clinical practice guidelines for histopathology reports of melanomas. Methods: A sample of melanoma histopathology reports in Queensland was audited for inclusion of recommended information. The quality of documentation was constructed and multivariate analysis used to determine factors affecting the quality of reporting practices. Results: Documentation of the most important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Previous research has explored various aspects of melanoma care in the Australian setting, 14,[16][17][18][19][20][21][22] including compliance with clinical practice guidelines, 15,[23][24][25][26][27] but not how GPs understand their multiple potential roles within melanoma patient care. The aim of the current study was to identify factors that affect GPs' confidence in, and attitudes towards, managing patients with suspected or confirmed melanoma, and how GPs explain their decisions to biopsy, treat, or refer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has explored various aspects of melanoma care in the Australian setting, 14,[16][17][18][19][20][21][22] including compliance with clinical practice guidelines, 15,[23][24][25][26][27] but not how GPs understand their multiple potential roles within melanoma patient care. The aim of the current study was to identify factors that affect GPs' confidence in, and attitudes towards, managing patients with suspected or confirmed melanoma, and how GPs explain their decisions to biopsy, treat, or refer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the final pathology diagnosis, whether correct or not, is ultimately responsible for determining which lesions enter into cancer registry databases [1]. This in turn may influence the results of epidemiological investigations of cancer, diagnostic studies, or comparative studies that rely upon evaluations provided by pathologists [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Using multivariate analysis, it was shown that one or more dermal mitoses per millimeter squared in thin melanomas was significantly associated with decreased survival . A limitation of this study and others is the lack of mitotic counts in a large proportion of the reports collected . A recent report suggested that a mitotic rate of three or more was correlated with clinical outcome, but another report focusing on thin melanomas (<1.0 mm in depth) failed to find a relationship between mitotic rate and sentinel lymph node status .…”
mentioning
confidence: 86%
“…2 A limitation of this study and others is the lack of mitotic counts in a large proportion of the reports collected. 3,4 A recent report suggested that a mitotic rate of three or more was correlated with clinical outcome, 5 but another report focusing on thin melanomas (<1.0 mm in depth) failed to find a relationship between mitotic rate and sentinel lymph node status. 6 Nonetheless, one mitosis is still currently sufficient to upstage a patient with a thin (≤1.0 mm) non-ulcerated melanoma to T1b.…”
mentioning
confidence: 99%